Improving Elementary Students Science Problem Solving Ability with HOTS-based LKPD - Ardiari, Ni Putu Asnita Eka; Wibawa, I Made Citra; Asril, Nice Maylani (Universitas Pendidikan Ganesha, 2023)
One of the demands of 21st century skills is the ability to think critically and problem solve. However, the implementation of science learning in elementary schools is still not optimal, indicated by the learning activites that is less student-oriented and has not stimulated students to think at a high level (HOTS). This study aims to develop HOTS-based LKPD. This type of research is development research using ADDIE modeling with five stages as follows analyze, design, development, implementation, and evaluation. The subject of this research is HOTS-based LKPD products, the object of this research is the validity, practicality, and effectiveness of HOTS-based LKPD products. The test subjects involved 25 fifth grade students with problem solving skills who were used as test objects. The data collection method used a questionnaire. This study encompasses both qualitative and quantitative analysis techniques. The results stated that the HOTS-based LKPD that had been developed received a material expert validity score of 92.38% and a learning media expert validity score of 94.50%. The teacher response practicality score was 97.49%, the individual test student response score was 96.36%, the small group test student response score was 95.75% so that it was declared valid and practical with E quality. The effectiveness test using the t-test method obtained a Sig value of 0.000 < 0.05. So that HOTS-based LKPD is effective in improving science problem solving skills.